The Effect of Intellectual Capital, Capital Structure, Activity Ratio on Profitability with Operating Cash Flow Moderation - Musthafa, Arizul Gayo; Alamsyah, Sustari; Hamdani, Hamdani; Zatira, Dhea (Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This research aims to analyze how capital structure, activity ratios, and intellectual capital influence profitability, with operating cash flow serving as a moderating variable, specifically within companies in the basic and chemical industries listed on the Indonesia Stock Exchange. The study sample consists of 31 companies selected based on the availability of annual reports from 2019 to 2023, using purposive sampling. The data analysis was conducted using panel data moderated regression through EViews12. The results indicate that both operating cash flow and intellectual capital have a positive effect on profitability. In contrast, capital structure has a negative impact, while activity ratios show no significant influence. Additionally, operating cash flow does not moderate the effects of capital structure or activity ratios, but it does moderate the relationship between intellectual capital and profitability.